The Problem of Human Sacrifice in Euripides’ "Iphigenia among the Taurians" - Maresca, Victoria; Perczyk, Cecilia J. (’Ilu. Revista de Ciencias de las Religiones, 2019)
The objective of this paper is to explore the problem of human sacrifice in Euripides’ tragedy Iphigenia among the Taurians. Although the archaeological surveys indicate that this type of sacrifices was not practiced in archaic and classical Greece, we find them repeatedly in Greek literature, in general, and more especially in the tragic genre, of which this work is a finished example. In this sense, we will focus our study on the role of allusions and references to human sacrifice in the tragedy, especially within the prologue, since we understand that it constitutes a central issue to the plot, as not only it relates to Iphigenia’s past but also conforms a constant threat to the other characters.